Indigenous Ecological Knowledge and Pastoralist Perception on Rangeland Management and Degradation in Guji Zone of South Ethiopia - Abate, Teshome (Consilience, 2016)
The study was conducted to explore range management practice, pastoralists’ views on degradation and its impact on local livelihood in south Ethiopia. The data was gathered from three pastoral and agro-pastoral districts of Guji zone using structure questionnaires, key informants and direct observation. The study shows the use of enclosure and herd mobility in basic traditional practice as well as the effectiveness of community indigenous knowledge is in assessing and monitoring rangeland degradation. Communities used numerous indicators to explain local level degradation, finding drought to be a primary cause in the decline in household livestock assets, expansion of aridity, and rising threat to food security. The study shows an alarming increase in degradation and the urgency of measures to halt this trend.